Relación de la ejecución presupuestal y los proyectos de inversión pública del Gobierno Regional de Loreto 2023 - Cornejo Saldaña, Limber (2025)
In this scientific study, the main objective was to demonstrate whether there is a relationship between the variables under study budget execution and the public investment projects of the Regional Government of Loreto 2023. Therefore, it was considered to carry out a quantitative and non-experimental study with samples of the figures executed in the current year of study, which we obtained from the MEF Friendly Consultation Transparency portal, from the SSI platform of Invierte.pe., and the SIAF of the institution under study. Well, once treated with the descriptive statistics, the study data gives us the following results: where the budget execution gives us a value of 50%, which indicates that it is moderate, and the public investment projects with 58%, which indicates that it is moderate. As the inferential statistics test was also carried out, it reflects that the study variables have no relationship since both variables have a Pearson correlation r = 0.117; which indicates that there is a direct positive relationship but at the same time it is very weak and a significance Sig = 0.718; which indicates that there is no statistical significance, therefore we proceeded to reject the main hypothesis and the hypotheses derived from the present investigation, it is also deduced and perceived that the elements of both variables are dispersed, which shows us the importance of statistical inference.